Housework, paid work and psychiatric symptoms Trabalho doméstico, trabalho assalariado e sintomas psiquiátricos - Vilma S Santana (Revista de Saúde Pública, 2001)
OBJECTIVE: To evaluate the hypothesis that work burden, the simultaneous engagement in paid work and unpaid family housework, is a potential risk factor for psychiatric symptoms among women. METHODS: A cross-sectional study was carried out with 460 women randomly selected from a poor area of the city of Salvador, Brazil. Women between 18 to 70 years old, who reported having a paid occupation or were involved in unpaid domestic activities for their families, were eligible. Work burden-related variables were defined as: a) double work shift, i.e., simultaneous engagement in a paid job plus unpaid housework; and b) daily working time. Psychiatric symptoms were collected through a validated questionnaire, the QMPA. RESULTS: Positive, statistically significant associations between high (>7 symptoms) QMPA scores and either double work shift (prevalence ratio -- PR=2.04, 95% confidence interval -- CI: 1.16, 2.29) or more than 10 hours of daily work time (PR=2.29, 95% CI: 1.96, 3.43) were found after adjustment for age, marital status and number of pre-school children. CONCLUSIONS: Major correlates of high QMPA scores are work burden variables. Being married or having pre-school children are also associated with high QMPA scores only when associated with work burden. OBJETIVO: Avaliar a hipótese de que a dupla carga de trabalho é um fator de risco potencial para sintomas psiquiátricos em mulheres. MÉTODOS: Estudo transversal realizado com 460 mulheres aleatoriamente selecionadas de uma área pobre da cidade de Salvador, BA, Brasil. Foram selecionadas mulheres entre 18 e 70 anos de idade, que referiram ter ocupação paga ou estar envolvidas com trabalho doméstico não remunerado para as suas famílias. A sobrecarga de trabalho foi analisada como: a) dupla jornada de trabalho, i.e., envolvimento simultâneo em trabalho pago e trabalho não pago para a família; e b) duração da jornada diária total de trabalho. Os sintomas psiquiátricos foram registrados por meio de um questionário psiquiátrico devidamente validado, o Questionário de Morbidade Psiquiátrica de Adultos (QMPA). RESULTADOS: Foram encontradas associações positivas, ajustadas por idade, estado civil e filhos em idade pré-escolar, entre escores altos do QMPA (>7 sintomas) e dupla jornada de trabalho (razão de prevalência, RP=2,04, 95% intervalo de confiança, IC: 1,16, 2,29) e mais que 10 horas de jornada de trabalho (RP=2,29, 95% IC: 1,96, 3,43). CONCLUSÕES: Os mais importantes fatores em associação com escores altos do QMPA foram as variáveis relacionadas ao trabalho. Ser casada ou ter crianças em idade pré-escolar na família estavam associadas a escores altos do QMPA apenas quando em combinação com a sobrecarga de trabalho.